Impact of rheological studies for pipeline transport of paraffinic crude oils - Rodríguez, Lilia; Vidales, H.umberto; Castañeda, Maribel; Leal, Gonzalo; Barrero, Rigoberto; Garzón, J. (CT&F - Ciencia, Tecnología y Futuro, 2000)
The results of this applied research contribute fundamental elements for handling paraffinic crude oils (pipeline design and operation) and the optimization of the use of Pour Point Depressor additives. The rheological studies support the fluid-dynamic analyses that accurately predict the pipeline transport operation, unlike traditional parameters such as pour point and cloud point. The evaluation of rheological behavior was carried out at the laboratory level in concentric viscometers and were scaled at the pilot plant level in a fluid-dynamic test circuit in pipes with diameters from 1.27 to 15.24 cm (1/2 to 6 inches), where the laboratory scale was confirmed. The tests were performed under strain rate temperature and conditions similar to those of pipeline and flowline operation in production fields. Also, the viability to restart pumping after a prolonged shutdown with extreme temperatures was calculated, evaluating creep stress. The study has allowed us to transport Cupiagua crude oil without the PPD additive in a segregated manner, showing that despite its high pour point 300K (27 °C), in dynamic conditions similar to those in the pipeline, the crude oil flows at temperatures near 283K (10 °C) without putting the integrity of the pipe in danger and within operational and equipment restrictions for the company operating the pipeline. This has generated significant savings, due to the additive as well as the possibility to segregate the crude oils, which facilitates the operation of the paraffin plant at the Barrancabermeja Industrial Complex.